Strategi Inovasi Produk dan Layanan sebagai Kunci Kesuksesan UMKM pada Usaha Bakso Simas di Pasar Bisnis yang Dinamis (Lembaga Pengembangan Kinerja Dosen, 2025)
Dynamic business markets require Micro, Small and Medium Enterprises (MSMEs) to continuously innovate in order to maintain competitiveness and increase business growth. This article discusses the product and service innovation strategies implemented by Bakso Simas Business in facing the challenges of a rapidly changing market. This research uses a qualitative method with a case study approach, where data is collected through interviews, observation, and documentation analysis. The results show that innovation in product variants, improving service quality, and utilizing digital technology are the main factors in increasing customer attractiveness and loyalty. In addition, differentiation strategies and adaptation to consumer trends play an important role in maintaining business sustainability. This study provides insights for MSME players in developing effective innovation strategies to face competition in a dynamic business market.